Binder composition for nonaqueous secondary battery electrodes, slurry composition for nonaqueous secondary battery electrodes, electrode for nonaqueous secondary batteries, and nonaqueous secondary battery
By controlling the redox potential and surface acidity of the binder composition, and combining a specific ratio of particulate polymers and water-soluble polymers, the problems of cycle characteristics, peeling characteristics and storage stability of non-aqueous secondary batteries were solved, and the adhesion of the electrodes and battery performance were improved.
Patent Information
- Application Number
- CN202480023627.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-19
- Filing Date
- 2024-04-12
- Publication Date
- 2025-11-21
AI Technical Summary
Existing non-aqueous secondary batteries have shortcomings in terms of cycle characteristics, peeling characteristics, and storage stability, especially the adhesion and storage stability of the electrode composite material layer need to be improved.
By controlling the redox potential in the binder composition and the total amount of acid on the surface of the particulate polymer and the amount of acid in the aqueous phase within a specific range, and by using a specific ratio of particulate polymer and water-soluble polymer, a highly efficient binder composition is formed for the preparation of non-aqueous secondary battery electrodes.
It achieves high cycle characteristics, high stripping characteristics and high storage stability of non-aqueous secondary batteries, reduces roller contamination and frictional heat during electrode manufacturing, and improves the overall performance of the battery.
Smart Images

Figure CN121002679A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to binder compositions for electrodes of non-aqueous secondary batteries, slurry compositions for electrodes of non-aqueous secondary batteries, electrodes for non-aqueous secondary batteries, and non-aqueous secondary batteries. Background Technology
[0002] Non-aqueous secondary batteries, such as lithium-ion batteries, typically have battery components including a positive electrode, a negative electrode, and spacers to isolate the positive and negative electrodes and prevent short circuits between them. These battery components are often formed as layered structures.
[0003] The positive and negative electrodes of non-aqueous secondary batteries can be formed by coating a slurry composition containing electrode active materials, binders, and dispersion media onto a suitable substrate such as a current collector, and then allowing the dispersion media to evaporate. Organic solvents are sometimes used as the dispersion media, but aqueous dispersion media with water as the main component are also sometimes used for ease of handling and to reduce environmental impact. Particulate polymers are widely used as binders. Various proposals have been made regarding aqueous slurry compositions containing aqueous dispersion media and binder compositions used to prepare such slurry compositions (e.g., Patent Documents 1 to 6).
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: International Publication No. 2015 / 098008;
[0007] Patent Document 2: International Publication No. 2015 / 129257;
[0008] Patent Document 3: International Publication No. 2015 / 098507;
[0009] Patent document 4: International Publication No. 2013 / 191239;
[0010] Patent document 5: International Publication No. 2019 / 188722 (corresponding publication: U.S. Patent Application Publication No. 2020 / 411870);
[0011] Patent document 6: Japanese Patent Application Publication No. 2022-064465 (corresponding publication: U.S. Patent Application Publication No. 2022 / 115665). Summary of the Invention
[0012] The problem the invention aims to solve
[0013] Non-aqueous secondary batteries require further performance improvements. For example, there is a need to further enhance the battery's cycle characteristics, that is, the ability to maintain capacity even after multiple charge-discharge cycles.
[0014] In addition, the electrode requires peeling properties, that is, the electrode composite layer has excellent adhesion to the current collector.
[0015] Furthermore, the binder composition used to form the slurry needs to be prepared in advance and used during slurry formation, thus requiring high storage stability.
[0016] Therefore, the object of the present invention is to provide: a binder composition for a non-aqueous secondary battery electrode that can achieve high cycle performance and has high peeling properties and high storage stability; an electrode that can achieve high cycle performance and has high peeling properties; and a non-aqueous secondary battery with high cycle performance.
[0017] Solution for solving the problem
[0018] To solve the above problems, the inventors discovered through research that by keeping the redox potential in the binder composition and the total amount of acid on the surface of the particulate polymer in the binder composition and the amount of acid in the aqueous phase within a specific range, the above problems can be solved, thus completing the present invention.
[0019] That is, the present invention provides the following content.
[0020] (1) A binder composition for a non-aqueous secondary battery electrode, comprising a particulate polymer and a dispersion medium, and having an aqueous phase and a solid phase,
[0021] The redox potential of the above-mentioned adhesive composition is 90–280 mV.
[0022] The total acid content on the surface of the above-mentioned particulate polymer and the total acid content in the above-mentioned aqueous phase is 0.15 mmol / g or more and 1.5 mmol / g or less.
[0023] (2) The binder composition for non-aqueous secondary battery electrodes according to (1), wherein the contents of Fe, Cu, Zn, Co, Ni and Cr are all less than 0.5 ppm.
[0024] (3) The binder composition for non-aqueous secondary battery electrodes according to (1) or (2), wherein the value obtained by dividing the amount of acid contained in the aqueous phase by the sum of the amount of acid in the aqueous phase and the amount of acid on the surface of the particulate polymer is 0.2 or more and 0.6 or less.
[0025] (4) The binder composition for a non-aqueous secondary battery electrode according to any one of (1) to (3), wherein the particulate polymer comprises one or more selected from styrene monomer units, butadiene monomer units, (meth)acrylate monomer units and acid-containing monomer units.
[0026] (5) The adhesive composition for a non-aqueous secondary battery electrode according to any one of (1) to (4), wherein the adhesive composition for a non-aqueous secondary battery electrode further comprises a water-soluble polymer.
[0027] (6) A slurry composition for a non-aqueous secondary battery electrode, comprising an electrode active material and a binder composition for a non-aqueous secondary battery electrode as described in any one of (1) to (5).
[0028] (7) An electrode for a non-aqueous secondary battery having an electrode composite material layer formed using the non-aqueous secondary battery electrode slurry composition described in (6).
[0029] (8) A non-aqueous secondary battery having a positive electrode, a negative electrode, a spacer and an electrolyte, wherein at least one of the positive electrode and the negative electrode is an electrode for the non-aqueous secondary battery as described in (7).
[0030] Invention Effects
[0031] According to the present invention, a binder composition for a non-aqueous secondary battery electrode that enables high cycle performance and has high peeling properties and high storage stability can be provided; an electrode that enables high cycle performance and has high peeling properties for a non-aqueous secondary battery; and a non-aqueous secondary battery with high cycle performance. Attached Figure Description
[0032] Figure 1 The graph illustrates the relationship between the cumulative amount (mmol) of hydrochloric acid added and the conductivity (mS) when determining the acidity of the surface of the particulate polymer and the acidity of the aqueous phase of the binder composition in the embodiments and comparative examples of this application. Detailed Implementation
[0033] The present invention will now be described in detail with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and can be implemented in any way without departing from the scope of the claims and their equivalents.
[0034] In the following description, the term "(meth)acrylic acid" means that it includes "acrylic acid", "methacrylic acid" and combinations thereof, such as (meth)acrylic acid refers to acrylic acid, methacrylic acid or mixtures thereof.
[0035] In polymers manufactured by copolymerizing multiple monomers, unless otherwise stated, the proportion of structural units formed by polymerizing a particular monomer in the polymer is usually consistent with the proportion of that particular monomer in all monomers used in the polymerization of the polymer (feed ratio).
[0036] In this application, the term "solid component" in a mixture of binder compositions, slurry compositions, etc., in which solids are dispersed in a liquid, is defined as the component remaining after the dispersion medium and solvent in the composition have evaporated and solidified, and the term "solid component concentration" is defined as the concentration of such component. When the composition consists of water and components dissolved or dispersed in water, the solid component concentration is the concentration of the components other than water.
[0037] (Adhesive composition)
[0038] The binder composition of the present invention comprises a particulate polymer and a dispersion medium, and has an aqueous phase and a solid phase. The aqueous phase consists of water and water-soluble components, and the solid phase is the particulate polymer; or a phase of particulate polymer and other water-insoluble solids.
[0039] Here, the particulate polymer is preferably a non-water-soluble particle. Unless otherwise stated, in this specification, "non-water-soluble" polymer particles mean that when 0.5g of the polymer is dissolved in 100g of water at a temperature of 25°C, the insoluble component is 90% by mass or more. On the other hand, unless otherwise stated, "water-soluble" polymer means that when 0.5g of the polymer is dissolved in 100g of water at a temperature of 25°C, the insoluble component is less than 1.0% by mass.
[0040] (Particulate polymer)
[0041] The particulate polymer functions as a binder when the binder composition is added to the slurry composition. When using this slurry composition to form an electrode composite layer, the particulate polymer bonds the components of the composite layer to each other or to the current collector. As the particulate polymer, a polymer capable of dispersing in an aqueous medium such as water can be used.
[0042] Here, known polymers that can be described as particulate polymers include diene polymers, acrylic polymers, fluoropolymers, and silicone polymers. These polymers can be used alone or in combination of two or more in any proportion.
[0043] Specifically, diene polymers are preferred as particulate polymers, particularly copolymers or hydrogenates thereof having aliphatic conjugated diene monomer units and aromatic vinyl monomer units. This is because particulate polymers composed of copolymers having aliphatic conjugated diene monomer units and aromatic vinyl monomer units can function well as adhesives. The aliphatic conjugated diene monomer units are repeating units with low rigidity and flexibility, which can improve adhesion, while the aromatic vinyl monomer units can reduce the solubility of the polymer in the electrolyte and improve the stability of the particulate polymer in the electrolyte.
[0044] When using a copolymer having aliphatic conjugated diene monomer units and aromatic vinyl monomer units as a particulate polymer, the aliphatic conjugated diene monomer capable of forming the aliphatic conjugated diene monomer unit is not particularly limited, and can include 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, substituted linear conjugated pentadienes, substituted and side-chain conjugated hexadienes, etc. One aliphatic conjugated diene monomer can be used alone, or two or more can be combined in any proportion.
[0045] In the particulate polymer, the content of aliphatic conjugated diene monomer units is preferably 20% by mass or more, more preferably 30% by mass or more, more preferably 70% by mass or less, and more preferably 60% by mass or less. When the content of aliphatic conjugated diene monomer units is 20% by mass or more, the flexibility of the negative electrode formed using the slurry composition can be improved. Furthermore, when the content of aliphatic conjugated diene monomer units is 70% by mass or less, the adhesive force of the particulate polymer is sufficiently high, enabling good adhesion between the components constituting the negative electrode composite layer and between the negative electrode composite layer and the current collector, thereby improving the peel strength of the negative electrode.
[0046] There are no particular limitations on the aromatic vinyl monomers that can form aromatic vinyl monomer units; styrene, α-methylstyrene, vinyltoluene, divinylbenzene, etc., can be used. Aromatic vinyl monomers can be used alone or in combination of two or more in any proportion.
[0047] Furthermore, in the particulate polymer, the content of aromatic vinyl monomer units is preferably 5% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, preferably 80% by mass or less, and more preferably 70% by mass or less. When the content of aromatic vinyl monomer units is 30% by mass or more, the electrolyte resistance of the negative electrode formed using the binder composition can be improved. In addition, when the content of aromatic vinyl monomer units is 80% by mass or less, the adhesive force of the particulate polymer composed of the copolymer is sufficiently high, which can well bond the components constituting the negative electrode composite layer to each other and to the current collector, thereby improving the peel strength of the negative electrode.
[0048] The copolymer having aliphatic conjugated diene monomer units and aromatic vinyl monomer units preferably contains 1,3-butadiene units as aliphatic conjugated diene monomer units and styrene units as aromatic vinyl monomer units (i.e., styrene-butadiene copolymer or hydrogenated styrene-butadiene copolymer).
[0049] From the viewpoint of imparting a desired surface acidity to particulate polymers, copolymers (particulate polymers) having aliphatic conjugated diene monomer units and aromatic vinyl monomer units preferably contain monomer units with acidic groups. Examples of monomer units containing acidic groups include olefinically unsaturated carboxylic acid monomer units and unsaturated monomer units having sulfonic acid groups. Among these, particulate polymers preferably contain olefinically unsaturated carboxylic acid monomer units.
[0050] Here, examples of olefinic unsaturated carboxylic acid monomers capable of forming olefinic unsaturated carboxylic acid monomer units include olefinic unsaturated monocarboxylic acids and their derivatives, olefinic unsaturated dicarboxylic acids and their anhydrides, and their derivatives.
[0051] Examples of olefinic unsaturated monocarboxylic acids and their derivatives include acrylic acid, methacrylic acid, crotonic acid, 2-ethylacrylic acid, isocrotonic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, α-chloro-β-E-methoxyacrylic acid, and β-diaminoacrylic acid.
[0052] Examples of olefinically unsaturated dicarboxylic acids and their derivatives include maleic acid, fumaric acid, itaconic acid, methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, diphenyl maleate, nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, and fluoroalkyl maleate. Furthermore, examples of anhydrides of olefinically unsaturated dicarboxylic acids include maleic anhydride, diacrylic anhydride, methylmaleic anhydride, and dimethylmaleic anhydride. Among these, olefinically unsaturated monocarboxylic acids are preferred, and acrylic acid is particularly preferred.
[0053] These can be used individually or in combination of two or more in any proportion.
[0054] Furthermore, examples of unsaturated monomers with sulfonic acid groups capable of forming unsaturated monomer units with sulfonic acid groups include vinyl sulfonic acid, methyl vinyl sulfonic acid, (meth)acrylate sulfonic acid, styrene sulfonic acid, ethyl (meth)acrylate-2-sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid. These can be used individually or in combination of two or more in any proportion.
[0055] Furthermore, in the particulate polymer, the content of the monomer unit containing acidic groups is preferably 1% by mass or more, more preferably 2% by mass or more, particularly preferably 3% by mass or more, and further preferably 15% by mass or less, more preferably 13% by mass or less, and particularly preferably 10% by mass or less. By setting the content of the monomer unit containing acidic groups to the lower limit or above mentioned above, it is easy to increase the surface acidity of the particulate polymer to the range desired in this application, thereby enabling excellent battery characteristics of the lithium-ion secondary battery while suppressing negative electrode expansion. On the other hand, by setting the content of the monomer unit containing acidic groups to the upper limit or below mentioned above, it is easy to prepare the particulate polymer.
[0056] Furthermore, the copolymer (particulate polymer) having aliphatic conjugated diene monomer units and aromatic vinyl monomer units preferably includes (meth)acrylate monomer units, and particularly preferably includes hydroxyl-containing (meth)acrylate monomer units having a (meth)acrylate structure and having hydroxyl groups.
[0057] Examples of hydroxyl-containing (meth)acrylate monomers capable of forming hydroxyl-containing (meth)acrylate monomer units include, for example, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, and 3-chloro-2-hydroxypropyl methacrylate. Among these, 2-hydroxyethyl acrylate is preferred.
[0058] These can be used individually or in combination of two or more in any proportion.
[0059] Furthermore, in the particulate polymer, the content of hydroxyl (meth)acrylate monomer units is preferably 0.5% by mass or more, more preferably 0.7% by mass or more, particularly preferably 0.8% by mass or more, preferably 10% by mass or less, more preferably 4% by mass or less, and particularly preferably 3% by mass or less. By setting the content of hydroxyl (meth)acrylate monomer units to the lower limit or above mentioned above, the copolymerization property of monomers containing acidic groups, such as olefinic unsaturated carboxylic acid monomers, with other monomers can be improved. On the other hand, by setting the content of hydroxyl (meth)acrylate monomer units to the upper limit or below mentioned above, the polymerization of hydroxyl (meth)acrylate monomers to form polymers can be suppressed, thereby improving the copolymerization property of olefinic unsaturated carboxylic acid monomers to the particulate polymer, thus enabling the copolymerization of the aforementioned monomers to proceed well.
[0060] Furthermore, the copolymers having aliphatic conjugated diene monomer units and aromatic vinyl monomer units may contain any other repeating units besides those described above, provided that they do not significantly impair the effects of the present invention.
[0061] The proportion of other repeating units is not particularly limited, but the upper limit is preferably 30% by mass or less, more preferably 4% by mass or less, and particularly preferably 2% by mass or less.
[0062] The proportion of particulate polymer in the binder composition of the present invention can be a desired proportion suitable for preparing the slurry composition. Furthermore, it can be appropriately adjusted to ensure good storage stability. Specifically, the proportion of particulate polymer relative to 100 parts by mass of electrode active material is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and on the other hand, preferably 10 parts by mass or less, more preferably 7 parts by mass or less.
[0063] Particulate polymers can be prepared by polymerizing monomer compositions containing the above-mentioned monomers in an aqueous medium.
[0064] In this invention, the proportion of each monomer in the monomer composition can be determined based on the proportion of monomer units (repeating units) in the particulate polymer.
[0065] There are no particular limitations on the aqueous medium, as long as it can disperse the particulate polymer in a particulate state. From the perspective of non-flammability and easy availability of a dispersion of particulate polymer particles, water is particularly preferred. Water can be used as the main solvent, and other solvents besides water can be mixed in within a range that ensures the dispersion of the particulate polymer particles.
[0066] The polymerization method is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, and emulsion polymerization can be used. The polymerization method can also be any method such as ionic polymerization, free radical polymerization, and living radical polymerization. From the perspective of manufacturing efficiency, such as the ease of obtaining high molecular weight compounds and the direct acquisition of polymers in a state dispersed in water without redispersibility, allowing them to be directly supplied to the binder compositions and slurry compositions of the present invention, emulsion polymerization is particularly preferred. Emulsion polymerization can be carried out using conventional methods. Furthermore, seed polymerization using seed particles can be employed in emulsion polymerization.
[0067] Moreover, the emulsifiers, dispersants, polymerization initiators, polymerization aids, etc. used in the polymerization can be conventional substances, and their dosage can also be conventional.
[0068] Furthermore, in order to manufacture the particulate polymer used in this invention, batch polymerization and semi-batch polymerization can be used, but semi-batch polymerization, in which monomers are added to the reaction system continuously or intermittently, is preferred. By using semi-batch polymerization, compared with batch polymerization in which acidic monomers such as olefinically unsaturated carboxylic acid monomers are added to the reaction system all at once from the beginning, the surface acidity of the particulate polymer can be more easily controlled.
[0069] As a method for preparing particulate polymers using semi-batch polymerization, for example, when the particulate polymer is the copolymer having aliphatic conjugated diene monomer units and aromatic vinyl monomer units as described above, it is preferable to continuously or intermittently add a primary monomer composition containing aliphatic conjugated diene monomers, aromatic vinyl monomers and monomers containing acidic groups to the reaction system, and then start adding a secondary monomer composition containing hydroxyl (meth)acrylic acid monomers after the monomer composition addition rate reaches 70% or more, thereby obtaining a particulate polymer.
[0070] "Continuous or intermittent addition" means that the monomer composition is not added to the reaction system all at once, but is added over a certain period of time (e.g., more than 30 minutes).
[0071] In addition, "monomer composition addition rate" refers to the proportion (by mass) of the monomers added to the reaction system to the total monomer composition used in the polymerization.
[0072] "Primary monomer composition" refers to the monomer composition added to the reaction system from the polymerization initiation stage. Preferably, 80-99% by mass, more preferably 90-99% by mass, of the total monomer composition used in the polymerization is included in the primary monomer composition. Furthermore, the primary monomer composition preferably contains aromatic vinyl monomers, aliphatic conjugated diene monomers, and monomers containing acidic groups; moreover, it preferably does not contain substantially any hydroxyl (meth)acrylate monomers.
[0073] In the preparation of particulate polymers using semi-batch polymerization, for example, a mixture of emulsifier, chain transfer agent, and water appropriately added to a primary monomer composition is added to a reaction vessel along with a separately prepared polymerization initiator, thereby initiating the polymerization reaction. The reaction conditions are not particularly limited, but the reaction temperature is preferably 60–90°C. Furthermore, the time from polymerization initiation to the monomer composition reaching 70% concentration is not particularly limited, but is preferably 2–6 hours, more preferably 3–5 hours.
[0074] Then, after the monomer composition addition rate reaches 70% or more (i.e., after 70% by mass of all monomer compositions used in polymerization has been added to the end of the reaction system), the secondary monomer composition containing hydroxyl (meth)acrylate monomers is added. There is no particular limitation on the time from the start of adding the secondary monomer composition to the end of its addition, but it is preferably 1 to 3 hours. By subsequently adding hydroxyl (meth)acrylate monomers in this way, the copolymerization of the acid-containing monomers with other monomers can proceed well, thereby making it easier to control the amount of surface acid.
[0075] Furthermore, the addition of the primary monomer composition and the secondary monomer composition can be completed separately or simultaneously. There is no particular limitation on the time from polymerization initiation to the completion of all monomer composition addition, but it is preferably 3 to 8 hours, more preferably 4 to 7 hours. Moreover, after the completion of all monomer composition addition, it is preferable to react at 0 to 90°C for 3 to 9 hours.
[0076] Then, the reaction is terminated by cooling when the polymerization conversion rate is sufficient (e.g., above 95%).
[0077] Here, the aqueous dispersion obtained after the above polymerization can be prepared into an aqueous dispersion of particulate polymer by adjusting the pH to a range typically 5 or higher, typically 10 or lower, and preferably 9 or lower, using an alkaline aqueous solution containing, for example, hydroxides of alkali metals (e.g., Li, Na, K, Rb, Cs), ammonia, inorganic ammonium compounds (e.g., NH4Cl), or organic amine compounds (e.g., ethanolamine, diethylamine). Using alkali metal hydroxides for pH adjustment is preferred because it can improve the peel strength of the negative electrode.
[0078] In addition, it is preferable to remove unreacted monomers by heating and vacuum distillation after adjusting the pH.
[0079] (Dispersion medium and components of the aqueous phase)
[0080] The binder composition of the present invention comprises a dispersion medium. In the binder composition, the dispersion medium and components soluble in the dispersion medium constitute an aqueous phase. Typically, in the binder composition of the present invention, particulate polymers are dispersed in the dispersion medium. In the binder composition of the present invention, the dispersion medium may be water; or a mixture of water and a water-soluble organic solvent, preferably water.
[0081] The binder composition of the present invention may contain a water-soluble polymer as a component constituting the aqueous phase. The water-soluble polymer is typically dissolved in water, which serves as the dispersion medium, to form the aqueous phase.
[0082] As an example of a water-soluble polymer, from the perspective of effectively adjusting the acidity in the aqueous phase, a polymer containing monomer units having acidic groups is preferred. As a monomer with acidic groups capable of forming monomer units having acidic groups, (meth)acrylic acid is preferred. Specifically, the water-soluble polymer is preferably poly(meth)acrylic acid, or a copolymer of (meth)acrylic acid with any other monomer. Examples of other arbitrary monomers include acrylonitrile, acrylamide, and other nitrile-containing vinyl monomers. The proportion of (meth)acrylic acid monomer units in 100% by mass of the water-soluble polymer is preferably 50% by mass or more and 100% by mass or less. The proportion of nitrile-containing vinyl monomer units in the water-soluble polymer is preferably 1% by mass or more and 29% by mass or less. By setting the proportions within this range, it is easy to prepare a binder composition with the desired acidity in the aqueous phase, thereby achieving the desired effects of the present invention.
[0083] The content of water-soluble polymer in the adhesive composition of the present invention can be appropriately adjusted to keep the acid content within a desired range. Specifically, the proportion of water-soluble polymer to 100% by mass of the total amount of the adhesive composition is preferably 0.5% by mass or more, and on the other hand, preferably 2.0% by mass or less.
[0084] The content of water-soluble polymer in the binder composition can also be specified relative to the mass of the particulate polymer. When the binder composition contains a water-soluble polymer, the amount of water-soluble polymer relative to 100 parts by mass of particulate polymer can be greater than 0 parts by mass and less than 10 parts by mass.
[0085] (Other ingredients)
[0086] In addition to the components described above, the binder composition of the present invention may also contain reinforcing materials, leveling agents, electrolyte additives, cellulose nanofibers, etc. These components can be appropriately selected to avoid affecting the battery reaction. For example, known components can be used, specifically those described in International Publication No. 2012 / 115096. These components can be used individually or in combination of two or more in any proportion.
[0087] (Surface acidity and aqueous phase acidity)
[0088] In the binder composition of the present invention, the total acidity on the surface of the particulate polymer and the acidity in the aqueous phase is a value within a specific range. Hereinafter, the acidity on the surface of the particulate polymer is sometimes simply referred to as "surface acidity." "Acidity" is an indicator reflecting the number of acidic groups per 1g of solid component in the binder composition. Therefore, when the binder composition consists of a particulate polymer, a water-soluble polymer, and water, the surface acidity is an indicator of the number of acidic groups on the surface of the particulate polymer per 1g of both the particulate polymer and the water-soluble polymer, and the acidity in the aqueous phase is an indicator of the number of acidic groups in the aqueous phase of each 1g of the particulate polymer and the water-soluble polymer.
[0089] The total amount of surface acid and acid in the aqueous phase is 0.15 mmol / g or more, preferably 0.20 mmol / g or more, more preferably 0.25 mmol / g or more, and on the other hand, it is 1.5 mmol / g or less, preferably 1.45 mmol / g or less, more preferably 1.40 mmol / g or less.
[0090] The binder composition of the present invention preferably has an aqueous phase acidity within a specific range as a proportion of the total aqueous phase acidity and surface acidity. Specifically, the value obtained by dividing the aqueous phase acidity by the total aqueous phase acidity and surface acidity is preferably 0.2 or more, more preferably 0.25 or more, even more preferably 0.30 or more, and on the other hand, preferably 0.6 or less, more preferably 0.55 or less, even more preferably 0.50 or less, and even more preferably 0.40 or less.
[0091] The acid content on the surface of the particulate polymer and the acid content in the aqueous phase of the binder composition can be determined by the following methods.
[0092] Add the binder composition diluted with water as needed to a glass container that has been rinsed with distilled water, set up a solution conductivity meter and stir. Continue stirring until the hydrochloric acid is added.
[0093] Add 0.1 equivalents of an aqueous sodium hydroxide solution to an aqueous dispersion containing particulate polymer to adjust the conductivity of the binder composition to 2.5–3.0 mS. Then, measure the conductivity after 6 minutes. This value is taken as the conductivity at the start of the measurement.
[0094] Add 0.5 mL of 0.1 equivalent hydrochloric acid to the adhesive composition, and measure the conductivity after 30 seconds. Then, add another 0.5 mL of 0.1 equivalent hydrochloric acid, and measure the conductivity after 30 seconds. Repeat this process of adding hydrochloric acid and measuring the conductivity after 30 seconds until the conductivity of the adhesive composition is higher than the conductivity at the start of the measurement.
[0095] The obtained conductivity data were plotted on a graph with conductivity (in mS) on the vertical axis (Y-axis) and the cumulative amount of added hydrochloric acid (in mmol) on the horizontal axis (X-axis). Thus, as... Figure 1 As shown, a hydrochloric acid concentration-conductivity curve with three bends (the points where the graph bends) was obtained. The X-coordinates of the three bends and the X-coordinate at the end of hydrochloric acid addition were assigned as P1, P2, P3, and P4, respectively, in ascending order of value. For the data in the intervals of X-coordinate from zero to P1, P1 to P2, P2 to P3, and P3 to P4, the approximate straight lines L1, L2, L3, and L4 were obtained using the least squares method. The X-coordinate of the intersection of L1 and L2 was assigned as A1 (mmol), the X-coordinate of the intersection of L2 and L3 as A2 (mmol), and the X-coordinate of the intersection of L3 and L4 as A3 (mmol).
[0096] The surface acidity of the particulate polymer per 1g of solid component of the adhesive composition and the acidity in the aqueous phase of the adhesive composition per 1g of solid component of the adhesive composition can be determined as milliequivalents (mmol / g) by titration with hydrochloric acid, respectively, according to formulas (a) and (b).
[0097] Formula (a): Surface acidity of particulate polymer per 1g solid component of the binder composition
[0098] (mmol / g)=(A2-A1) / (mass of solid components in the binder composition (g))
[0099] Formula (b): Acidity in the aqueous phase per 1g of solid component of the binder composition.
[0100] (mmol / g)=(A3-A2) / (mass of solid components in the binder composition (g))
[0101] The surface acidity of particulate polymers can be adjusted by changing the type and amount of monomers used to manufacture the polymer as a particulate polymer. Specifically, for example, increasing the amount of monomers containing acidic groups, such as monomers containing carboxylic acid groups, can increase the surface acidity.
[0102] The amount of acid in the aqueous phase can be adjusted by changing the type and amount of components such as water-soluble polymers that exist in a dissolved state in the aqueous phase.
[0103] (Redox potential)
[0104] The redox potential of the adhesive composition of the present invention is a value within a specific range. Specifically, the redox potential is 90 mV or more, preferably 100 mV or more, more preferably 110 mV or more, and on the other hand, it is 280 mV or less, preferably 270 mV or less, more preferably 250 mV or less.
[0105] Redox potentials can be measured using a potentiometer with appropriate electrodes. Specifically, they can be measured at 25°C using a platinum composite ORP electrode (e.g., HORIBA composite electrode 9300-10D).
[0106] The redox potential of an adhesive composition is affected by the surface acidity, the acidity in the aqueous phase, their total amount, and the ratio of the acidity in the aqueous phase to their total amount. Therefore, the redox potential of the adhesive composition can be adjusted by changing the type (especially the type and proportion of acid-containing monomer units) and amount of the particulate polymer and the components added to the aqueous phase.
[0107] In addition, the redox potential of the binder composition is also affected by the content of the metal component and the timing of the addition of each component when preparing the binder composition. Therefore, it is sometimes possible to adjust the redox potential to the desired value by properly controlling these factors.
[0108] The inventors have discovered that by setting the total surface acidity of the particulate polymer in the binder composition to the total acidity in the aqueous phase, and the redox potential to values within the aforementioned specific range, the storage stability of the binder composition can be improved. Furthermore, the peel characteristics of electrodes manufactured using this binder composition can be improved. Additionally, the cycle characteristics of non-aqueous secondary batteries having electrodes manufactured using this binder composition can be improved. Moreover, during the formation of electrodes using this binder composition, the degree of roller contamination during pressing operations such as those performed by roller presses or other roller-based processes, and during operations where the electrode composite layer contacts the rollers, can be reduced. While the principle underlying these effects is not yet fully understood, it is believed that by satisfying the aforementioned conditions for acidity and redox potential, the amount of low molecular weight substances such as free oligomers can be reduced, thereby improving storage stability and peel characteristics. Furthermore, the amount of low molecular weight substances migrating to the surface of the layer due to frictional heat generated during the pressing process of the electrode composite layer in electrode manufacturing using a slurry containing the binder composition can be reduced, thereby improving peel characteristics, cycle characteristics, and reducing roller contamination.
[0109] By ensuring that the proportion of aqueous phase acid in the total amount of surface acid and aqueous phase acid is within the aforementioned specific range, the aforementioned effects can be further obtained effectively. Although the principle behind obtaining such effects is not yet clear, one reason is that when the amount of acid in the aqueous phase is excessive, the viscosity of the binder composition tends to increase over time, impairing storage stability and consequently adversely affecting cycling characteristics, etc. Therefore, by ensuring that the proportion of aqueous phase acid is within the aforementioned range, such adverse effects can be avoided.
[0110] (Metal content)
[0111] The binder composition of the present invention preferably has a low metal content. Specifically, under normal circumstances, the elements that have a substantial impact on the metal content are Fe, Cu, Zn, Co, Ni, and Cr. Therefore, the content of each of these elements is determined, and preferably, the content of each element is less than 0.5 ppm. The metal content can be determined using ICP-MS after appropriate pretreatment of the binder composition. The lower limit of the metal content is ideally 0 ppm, but it can also be greater than 0 ppm.
[0112] By suppressing the metal content to the aforementioned low level, not only can the redox potential be adjusted to the desired value, but the capacity of the battery made using the binder composition can also be increased.
[0113] As a method to reduce the metal content of an adhesive composition to below 0.5 ppm, besides using materials with low metal content as the materials for preparing the adhesive composition, methods include removing metal components from the prepared adhesive composition. Examples of operations for removing metal components include removing magnetic substances using magnetism. Since the main component of metal is magnetic metals such as iron, the metal content can be reduced by removing magnetic substances. Examples of magnetic substance removal devices utilizing magnetism include magnetic separators sold by Magnetics Co., Ltd. of Japan and magnetic filters sold by TokEngineering Co., Ltd.
[0114] (Slurry composition for non-aqueous secondary battery electrodes)
[0115] The non-aqueous secondary battery electrode slurry composition of the present invention comprises an electrode active material and the binder composition for non-aqueous secondary battery electrodes described above. The slurry composition of the present invention can be used as a slurry composition for both negative and positive electrodes, but is particularly preferred as a slurry composition for negative electrodes. Specific examples of the slurry composition for negative electrodes will be described below.
[0116] The amount of binder composition added to the slurry composition can be appropriately adjusted to achieve a desired ratio of particulate polymer to active material. Specifically, the ratio of particulate polymer to active material is preferably 0.5 parts by mass or more, and more preferably 5.0 parts by mass or less. By keeping the amount of particulate polymer within the above range, the effects of the present invention described above can be well obtained. Furthermore, if the amount of particulate polymer is above the lower limit, the components constituting the electrode composite layer can be well bonded to each other and to the current collector, thereby improving the peel strength of the electrode. Furthermore, if the amount of particulate polymer is below the upper limit, the productivity of the slurry composition and the cycle characteristics of the secondary battery can be ensured.
[0117] (Active substances)
[0118] The active material that can be contained in the slurry composition of the present invention can be appropriately selected from materials commonly used in non-aqueous secondary batteries. Examples of negative electrode active materials include carbon-based negative electrode active materials, non-carbon-based negative electrode active materials, and active materials composed of combinations thereof.
[0119] Examples of carbon-based anode active materials include carbonaceous materials and graphitic materials.
[0120] Carbonaceous materials are materials with low graphitization (i.e., low crystallinity) obtained by heat-treating carbon precursors at temperatures below 2000°C. Furthermore, there is no particular limitation on the lower limit of the heat treatment temperature for carbonization; for example, it can be above 500°C. Examples of carbonaceous materials include easily graphitizable carbon, whose structure can be readily altered by heat treatment temperature; and non-graphitizable carbon, represented by glassy carbon, which has a near-amorphous structure.
[0121] Examples of graphitizable carbon materials include carbon materials made from tar pitch obtained from petroleum or coal. Specific examples include coke, mesophase carbon microspheres (MCMB), mesophase pitch-based carbon fibers, and pyrolysis-grown carbon fibers.
[0122] Examples of non-graphitized carbon include phenolic resin sintered bodies, polyacrylonitrile-based carbon fibers, quasi-isotropic carbon, furfuryl alcohol resin (PFA) sintered bodies, and hard carbon.
[0123] Graphitic materials are obtained by heat-treating easily graphitized carbon at temperatures above 2000°C, resulting in materials with high crystallinity approaching that of graphite. Furthermore, there is no particular upper limit to the heat treatment temperature; for example, it can be set below 5000°C.
[0124] Examples of graphitic materials include natural graphite and synthetic graphite.
[0125] Examples of artificial graphite include: artificial graphite obtained by heat-treating carbon containing easily graphitized carbon at temperatures above 2800°C; graphitized MCMB obtained by heat-treating MCMB at temperatures above 2000°C; and graphitized mesophase pitch-based carbon fibers obtained by heat-treating mesophase pitch-based carbon fibers at temperatures above 2000°C.
[0126] In addition to the above, another well-known carbon-based anode active material is the composite carbon material described in Japanese Patent Application Publication No. 2013-45714, which is formed by forming a film of low-crystallinity carbon on the surface of core particles composed of highly crystalline carbon.
[0127] Non-carbon-based anode active materials are active materials other than carbon-based anode active materials. Examples of non-carbon-based anode active materials include metal-based anode active materials.
[0128] Metal-based anode active materials are active materials containing metals. They typically refer to active materials whose structure includes elements capable of intercalating lithium, and whose theoretical capacity per unit mass when lithium is intercalated is 500 mAh / g or higher. Examples of metal-based anode active materials include lithium metal, elemental metals capable of forming lithium alloys (such as Ag, Al, Ba, Bi, Cu, Ga, Ge, In, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, etc.) and their alloys, as well as their oxides, sulfides, nitrides, silicides, carbides, phosphides, etc.
[0129] Among metal-based anode active materials, silicon-based active materials are preferred (silicon-based anode active materials). This is because, by using silicon-based anode active materials, the capacity of lithium-ion secondary batteries can be increased.
[0130] Examples of silicon-based anode active materials include silicon (Si), silicon-containing alloys, SiO, SiOx, and composites of Si-containing materials and conductive carbon formed by coating or compositing Si-containing materials with conductive carbon. Furthermore, these silicon-based anode active materials can be used alone or in combination of two or more.
[0131] Examples of silicon-containing alloys include, for instance, alloy compositions containing silicon and at least one element selected from titanium, iron, cobalt, nickel, and copper.
[0132] In addition, examples of silicon-containing alloys include alloy compositions containing transition metals such as silicon, aluminum, and iron, and further containing rare earth elements such as tin and yttrium.
[0133] SiOx is a compound containing at least one of SiO and SiO2, and Si, where x is typically 0.01 or more and less than 2. Furthermore, SiOx can be formed, for example, by the disproportionation reaction of silicon monoxide (SiO). Specifically, SiOx can be prepared by heat-treating SiO in the presence of a polymer such as polyvinyl alcohol to generate silicon and silicon dioxide. The heat treatment can be performed at a temperature of 900°C or higher, preferably 1000°C or higher, in an atmosphere containing organic gases and / or vapors after SiO has been pulverized and mixed with any polymer.
[0134] Examples of compounds containing Si materials and conductive carbon include those obtained by heat-treating a pulverized mixture of SiO, polymers such as polyvinyl alcohol, and any carbon material in an atmosphere containing, for example, organic gases and / or vapors. Furthermore, these compounds can also be obtained by known methods such as coating the surface of SiO particles using chemical vapor deposition with organic gases, or granulating SiO particles with graphite or artificial graphite through mechanochemical treatment.
[0135] When the electrode slurry composition of the present invention is a negative electrode slurry composition and contains both carbon-based and non-carbon-based negative electrode active materials, the proportion of non-carbon-based negative electrode active materials in a total of 100% by mass is preferably greater than 0% by mass and less than 20% by mass. With such a proportion, the effects of the present invention can be well obtained.
[0136] (Preparation of slurry composition)
[0137] The slurry composition for secondary battery electrodes of the present invention can be prepared by dispersing the above-mentioned components in an aqueous medium as the dispersion medium. Specifically, the slurry composition can be prepared by mixing the above-mentioned components with an aqueous medium using a ball mill, sand mill, bead mill, pigment disperser, grinder, ultrasonic disperser, homogenizer, planetary mixer, FILMIX, or other mixers.
[0138] Here, water is typically used as the aqueous medium, but aqueous solutions of any compound or mixtures of a small amount of organic medium and water can also be used. Furthermore, the concentration of the solid components in the slurry composition can be such that the components are uniformly dispersed, for example, 30% by mass or more and 90% by mass or less. Moreover, the mixing of the aforementioned components with the aqueous medium can typically be carried out at a temperature range of room temperature or above and 80°C or below for 10 minutes or more and several hours.
[0139] (Electrodes for secondary batteries)
[0140] The electrode for secondary batteries of the present invention can be manufactured using the slurry composition for secondary battery electrodes of the present invention.
[0141] Here, the electrode for a secondary battery of the present invention has a current collector and an electrode composite material layer formed on the current collector, the electrode composite material layer being obtained from the slurry composition for a secondary battery electrode of the present invention. Furthermore, each component included in the electrode composite material layer is a component contained in the slurry composition for a secondary battery electrode of the present invention, and the preferred proportions of these components are the same as the preferred proportions of the components in the slurry composition for a secondary battery electrode.
[0142] Furthermore, the electrode for secondary batteries of the present invention can suppress the expansion of the battery cells of the secondary battery, while enabling the secondary battery to exhibit excellent cycle characteristics.
[0143] (Manufacturing method of electrodes for secondary batteries)
[0144] The electrode for a secondary battery of the present invention can be manufactured by, for example, the following steps: applying the above-mentioned slurry composition for a secondary battery electrode onto a current collector (coating step); and drying the slurry composition for a secondary battery electrode applied onto the current collector to form an electrode composite material layer on the current collector (drying step).
[0145] (Coating process)
[0146] There are no particular limitations on the method for applying the aforementioned secondary battery electrode slurry composition to the current collector, and known methods can be used. Specifically, as the coating method, methods such as doctor blade coating, dip coating, reverse roller coating, direct roller coating, gravure coating, extrusion coating, and brush coating can be used. In this case, the slurry composition can be applied to only one side of the current collector or to both sides. The thickness of the slurry film before drying can be appropriately set according to the thickness of the electrode composite material layer obtained after drying.
[0147] Here, a material with conductivity and electrochemical durability can be used as the current collector in the coating slurry composition. Specifically, current collectors made of materials such as iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, and platinum can be used, and copper foil is particularly preferred as the current collector used as the electrode. Furthermore, the above-mentioned materials can be used alone or in combination of two or more in any proportion.
[0148] (Drying process)
[0149] The method for drying the slurry composition on the current collector is not particularly limited, and known methods can be used, such as drying with warm air, hot air, or low-humidity air; vacuum drying; drying by irradiation with infrared rays, electron beams, etc. By drying the slurry composition on the current collector in this way, an electrode composite material layer can be formed on the current collector, resulting in an electrode for a secondary battery having both a current collector and an electrode composite material layer.
[0150] In addition, after the drying process, a die press or roller press can be used to apply pressure to the electrode composite layer. This pressure treatment can improve the peel strength of the electrode.
[0151] (Secondary battery)
[0152] The secondary battery of the present invention includes a positive electrode, a negative electrode, an electrolyte, and a spacer, and uses the electrode for secondary batteries of the present invention as at least one of the positive and negative electrodes. Furthermore, because the secondary battery of the present invention uses the electrode for secondary batteries of the present invention, it is able to suppress battery cell expansion and exhibit excellent battery characteristics such as rate performance. The following description uses a lithium-ion secondary battery with the negative electrode as the electrode for secondary batteries of the present invention as an example to illustrate the positive electrode, electrolyte, and spacer; however, the present invention is not limited to these examples.
[0153] (positive electrode)
[0154] As the positive electrode, known positive electrodes used as positive electrodes for lithium-ion secondary batteries can be used. Specifically, as the positive electrode, a positive electrode formed by forming a positive electrode composite material layer on the current collector can be used.
[0155] Furthermore, as the current collector, a current collector made of metallic materials such as aluminum can be used. Additionally, as the positive electrode composite layer, a layer containing known positive electrode active materials, conductive materials, and binder materials can be used.
[0156] (electrolyte)
[0157] As an electrolyte, an electrolyte in which the electrolyte is dissolved in a solvent can be used.
[0158] Here, an organic solvent capable of dissolving electrolytes can be used as the solvent. Specifically, a solvent prepared by adding viscosity-adjusting solvents such as 2,5-dimethyltetrahydrofuran, tetrahydrofuran, diethyl carbonate, methyl ethyl carbonate, dimethyl carbonate, methyl acetate, dimethoxyethane, dioxane, methyl propionate, and methyl formate to an alkyl carbonate solvent such as ethylene carbonate, propylene carbonate, and γ-butyrolactone can be used.
[0159] Lithium salts can be used as electrolytes. Among these lithium salts, those described in Japanese Patent Application Publication No. 2012-204303 are preferred, considering their ease of solubility in organic solvents and high degree of dissociation.
[0160] (spacer)
[0161] As a spacer, spacers such as those described in Japanese Patent Application Publication No. 2012-204303 can be used. Among these, from the viewpoint of increasing the capacity per unit volume by thinning the overall film thickness of the spacer, thereby increasing the ratio of electrode active material in the lithium-ion secondary battery, a microporous membrane made of polyolefin resin (polyethylene, polypropylene, polybutene, polyvinyl chloride) is preferred.
[0162] (Manufacturing method of secondary batteries)
[0163] The secondary battery of the present invention can be manufactured, for example, by overlapping the positive and negative electrodes with a spacer between them, winding or folding them according to the desired battery shape, placing them in a battery container, injecting electrolyte into the battery container, and sealing it. To prevent internal pressure rise, overcharging, or over-discharging, overcurrent protection components such as fuses and PTC elements, porous metal mesh, and conductive plates can be provided as needed. The secondary battery can be any shape, such as coin-shaped, button-shaped, sheet-shaped, cylindrical, square, or flat.
[0164] Example
[0165] The following embodiments illustrate the present invention. However, the present invention is not limited to the following embodiments and can be modified and implemented in any way without departing from the scope of the claims and their equivalents.
[0166] In the following instructions, unless otherwise specified, "%" and "parts" refer to quantities based on mass. Furthermore, unless otherwise specified, the operations described below are performed under normal temperature and pressure conditions.
[0167] [Evaluation Method]
[0168] (Redox potential)
[0169] After placing 50g of the binder composition in a sealed 25°C constant temperature bath for 30 minutes, a platinum composite ORP electrode (HORIBA composite electrode 9300-10D) was immersed in the binder composition, and the redox potential (mV) was measured.
[0170] (Surface acidity of particulate polymers and aqueous phase acidity of binder compositions)
[0171] The surface acidity (mmol / g) of the particulate polymer per 1g of solid component of the adhesive composition and the acidity (mmol / g) in the aqueous phase of the adhesive composition per 1g of solid component of the adhesive composition were determined by the following procedures.
[0172] Rinse a 150ml glass container with distilled water. Add 50g of water to the container to dilute the binder composition to a 2% concentration. Set the container to a solution conductivity meter (Kyoto Electronics Industries, Ltd.: CM-117, using battery cell type: K-121) and stir. Continue stirring until the hydrochloric acid addition is complete. Add 0.1 equivalents of sodium hydroxide (Wako Pure Chemical Industries, Ltd.: Reagent Grade) to the binder composition to achieve a conductivity of 2.5–3.0 mS. Measure the conductivity after 6 minutes. This value is taken as the conductivity at the start of the measurement. Add 0.5ml of 0.1 equivalents of hydrochloric acid (Wako Pure Chemical Industries, Ltd.: Reagent Grade) to the binder composition and measure the conductivity after 30 seconds. Immediately after the measurement, add another 0.5ml of 0.1 equivalents of hydrochloric acid and measure the conductivity after 30 seconds. Repeat the process of adding hydrochloric acid and measuring conductivity after 30 seconds until the conductivity of the binder composition is higher than the conductivity at the start of the measurement.
[0173] Typically, when titrating binder compositions containing acids in both the surface of particulate polymers and the aqueous phase, and plotting the resulting conductivity data on a graph with conductivity (mS) on the vertical axis and the cumulative amount of added hydrochloric acid (mmol) on the horizontal axis, such titrations are performed. Figure 1 As shown, a hydrochloric acid concentration-conductivity curve with three bends (the points where the graph bends) can be obtained. The X-coordinates of the three bends and the X-coordinate at the end of hydrochloric acid addition are assigned to P1, P2, P3, and P4 in ascending order of value. For the data within the intervals of X-coordinate from zero to P1, P1 to P2, P2 to P3, and P3 to P4, respectively, approximate straight lines L1, L2, L3, and L4 are obtained using the least squares method. The X-coordinate of the intersection of L1 and L2 is assigned to A1 (mmol), the X-coordinate of the intersection of L2 and L3 is assigned to A2 (mmol), and the X-coordinate of the intersection of L3 and L4 is assigned to A3 (mmol).
[0174] The surface acidity of the particulate polymer per 1g of solid component of the binder composition and the acidity in the aqueous phase of the binder composition per 1g of solid component of the binder composition are calculated as milliequivalents (mmol / g) of hydrochloric acid using formulas (a) and (b), respectively.
[0175] Formula (a): Surface acidity of particulate polymer per 1g solid component of the binder composition
[0176] (mmol / g)=(A2-A1) / (mass of solid components in the binder composition (g))
[0177] Formula (b): Acidity in the aqueous phase per 1g of solid component of the binder composition.
[0178] (mmol / g)=(A3-A2) / (mass of solid components in the binder composition (g))
[0179] (Metal content)
[0180] The metal content of the binder composition was determined using ICP-MS. The metal elements to be determined were Fe, Cu, Zn, Co, Ni, and Cr.
[0181] (Peel strength)
[0182] The prepared lithium-ion secondary battery was cut into rectangular test pieces with a width of 1.0 cm and a length of 10 cm using the negative electrode. The test pieces were fixed with the negative electrode composite layer side facing upwards. Cellophane tape was then applied to the negative electrode composite layer side of the test piece. Cellophane tape conforming to JIS Z1522 was used. The cellophane tape was then peeled off from one end of the test piece at a speed of 50 mm / min along a 180° direction (towards the other end of the test piece), and the stress was measured. This measurement was repeated 10 times, and the average stress was taken as the peel strength (N / m), and evaluated according to the following criteria. A higher peel strength indicates better adhesion of the negative electrode composite layer to the current collector.
[0183] A: Peel strength is above 8 N / m
[0184] B: Peel strength is above 5N / m and below 8N / m
[0185] C: Peel strength is above 3N / m and below 5N / m
[0186] D: Peel strength less than 3 N / m
[0187] (Maintain stability)
[0188] After measuring the viscosity (in mPa·s) of the binder composition using a Type B viscometer, it was stored in an oven heated to 40°C for one week. After storage, the viscosity was measured again using a Type B viscometer, and the viscosity change was calculated according to the following formula and evaluated according to the following evaluation criteria.
[0189] Viscosity change (%) = (Viscosity of the adhesive composition after storage) / (Viscosity of the adhesive composition before storage)
[0190] (viscosity of the composition) × 100
[0191] A: Less than 110%
[0192] B: 110% or more but less than 120%
[0193] C: 120% or more but less than 130%
[0194] D: Over 130%
[0195] (Cyclic Characteristics)
[0196] The secondary battery was left to stand at 25°C for 6 hours. Then, it was charged at 0.1C constant current for 100 minutes at 25°C. Next, it underwent an aging process at 60°C for 12 hours. Following this, a charge-discharge cycle was performed at 25°C, charging to a cell voltage of 4.20V and discharging to a cell voltage of 2.75V using a 0.5C constant current method, and the initial capacity C0 was measured. This charge-discharge cycle was repeated, and the capacity C1 was measured after 50 cycles. The capacity retention rate C2 was then calculated using the following formula.
[0197] C2(%))(C1 / C0)×100
[0198] The higher the value of the capacity retention rate C2, the better the cycling performance.
[0199] A: Capacity retention rate C2 is above 90%.
[0200] B: Capacity retention rate C2 is above 85% and less than 90%.
[0201] C: Capacity retention rate C2 is above 80% and below 85%.
[0202] D: Capacity retention rate C2 is less than 80%.
[0203] (Example 1)
[0204] (1-1. Preparation of particulate polymer A)
[0205] In container A, 99 parts of the monomer composition, 0.25 parts of tert-dodecyl mercaptan as a chain transfer agent, and 0.35 parts of sodium lauryl sulfate as an emulsifier were added to prepare a mixture containing the monomer composition. The monomer composition was composed of 42.0 parts of styrene as an aromatic vinyl monomer, 54.0 parts of 1,3-butadiene as an aliphatic conjugated diene monomer, and 3.0 parts of itaconic acid as an acidic monomer.
[0206] On the other hand, prepare 1 part of potassium persulfate as a polymerization initiator.
[0207] The mixture is initially added from container A in small amounts to pressure container B, while the polymerization initiator is simultaneously added in small amounts to pressure container B, thereby initiating the polymerization reaction. The reaction temperature is maintained at 75°C.
[0208] After adding approximately 70% of the total monomer composition, add 1 part of 2-hydroxyethyl acrylate as a hydroxy (meth)acrylate monomer to pressure vessel B in small amounts each time.
[0209] After 5.5 hours of polymerization initiation, the full amount of these monomer compositions was added, and then the mixture was further heated to 85°C to carry out the reaction.
[0210] The reaction was terminated by cooling at a polymerization conversion rate of 97%, yielding a mixture containing particulate polymer. A 5% sodium hydroxide aqueous solution was added to this mixture to adjust the pH to 8. Unreacted monomers were then removed by heated vacuum distillation. Further cooling yielded an aqueous dispersion containing particulate polymer A.
[0211] (1-2. Preparation of water-soluble polymers)
[0212] 100 parts of a water-soluble polymer monomer composition were added to a polymerization reactor, and the temperature was raised to 85°C. The water-soluble polymer monomer composition is a composition consisting of 75.0 parts of acrylic acid as a (meth)acrylic acid monomer and 25.0 parts of acrylonitrile as a nitrile-containing vinyl monomer.
[0213] Midway through the heating process, when the system temperature reached 60°C, 1.3 parts of 2,2'-azobis(2-methyl-N-2-hydroxyethylpropionamide) were added as a polymerization initiator. The mixture was then stirred at 85°C. The reaction was terminated by cooling when the monomer conversion reached over 90%. The pH was then adjusted to 8.0 with a 4% sodium hydroxide aqueous solution, and unreacted monomers were removed by heated vacuum distillation to obtain an aqueous solution of the water-soluble polymer.
[0214] (1-3. Adhesive composition)
[0215] To 100 parts (based on solid content) of an aqueous dispersion containing particulate polymer A obtained in (1-1), 0.5 parts (based on the mass of water-soluble polymer) of an aqueous solution of water-soluble polymer obtained in (1-2) were added, and the mixture was passed through a magnetic filter. Water was further added to adjust the concentration. This yielded an aqueous dispersion containing particulate polymer A and a water-soluble polymer as a binder composition. The solid content concentration of the binder composition was 40%. The redox potential, surface acidity, acidity in the aqueous phase, and metal content of the binder composition were measured. Furthermore, the storage stability of the binder composition was evaluated. The results are shown in Table 1.
[0216] (1-4. Carbon-based anode active materials)
[0217] Artificial graphite (average particle size: 24.5 μm, interlayer distance of graphite (interface spacing (d value) of (002) plane determined by X-ray diffraction): 0.354 nm) was prepared as a carbon-based negative electrode active material.
[0218] (1-5. Slurry composition for negative electrode of lithium-ion secondary battery)
[0219] In a planetary mixer equipped with a disperser, 85 parts of carbon-based negative electrode active material A obtained from (1-4) as the negative electrode active material, 15 parts of silicon-carbon composite active material as the Si-based active material, 1.5 parts of carboxymethyl cellulose (1% by mass aqueous solution viscosity: 250 mPa·s) and 1 part of acetylene black (BET specific surface area: 68 m²) as the conductive material were added. 2 / g). After adjusting their mixture to a solids concentration of 56% with ion-exchanged water, they were mixed at 25°C for 60 minutes. Then, after adjusting to a solids concentration of 52% with ion-exchanged water, they were further mixed at 25°C for 15 minutes to obtain the mixture.
[0220] Add 1.6 parts (based on the mass of particulate polymer A) of the binder composition obtained in (1-3) and ion-exchanged water to the above mixture, adjust to a final solid content concentration of 50%, and mix for another 10 minutes. Degas the mixture under reduced pressure to obtain a slurry composition for the negative electrode of a lithium-ion secondary battery.
[0221] (1-6. Negative electrode of lithium-ion secondary battery)
[0222] The lithium-ion secondary battery negative electrode slurry composition obtained in (1-5) was applied using a corner-shaped coating machine at a coating amount of 9-10 mg / cm². 2 The slurry composition for lithium-ion secondary battery anodes is applied to a 15 μm thick copper foil, which serves as the current collector. The copper foil coated with this slurry composition is then conveyed at 0.5 m / min in an oven at 60°C for 2 minutes to dry it. Afterward, it is heated in an oven at 120°C for 2 minutes to obtain the anode raw material.
[0223] The obtained negative electrode raw material was pressed using a roller press to make the density of the negative electrode composite layer 1.6–1.7 g / cm³. 3 A negative electrode for lithium-ion secondary batteries was obtained. The peel strength of this negative electrode for lithium-ion secondary batteries was evaluated. The results are shown in Table 1.
[0224] (1-7. Positive electrode of lithium-ion secondary battery)
[0225] In a planetary mixer, 100 parts of LiCoO2 as the positive electrode active material, 2 parts of acetylene black (manufactured by Denka Co., Ltd., HS-100) as the conductive material, and 2 parts of PVDF (polyvinylidene fluoride, manufactured by Kureha Chemical Co., Ltd., KF-1100) as the binder material were added, and 2-methylpyrrolidone was further added to make the total solid content concentration 67%. The mixture was then mixed to prepare a slurry composition for the positive electrode of a lithium-ion secondary battery.
[0226] The obtained lithium-ion secondary battery positive electrode slurry composition was coated onto a 20 μm thick aluminum foil, which served as the current collector, using a corner-shaped coating machine. The aluminum foil coated with the lithium-ion secondary battery positive electrode slurry composition was then conveyed at a speed of 0.5 m / min in an oven at 60°C for 2 minutes to dry it. Afterwards, it was heat-treated in an oven at 120°C for 2 minutes to obtain the positive electrode raw material.
[0227] The obtained cathode raw material was pressed using a roller press to achieve a density of 3.40–3.50 g / cm³ for the cathode composite layer. 3 This yields the positive electrode for lithium-ion secondary batteries.
[0228] (1-8. Lithium-ion secondary batteries)
[0229] Cut a single-layer polypropylene spacer (65mm wide, 500mm long, 25μm thick; manufactured by dry process; porosity 55%) to obtain a rectangular spacer of 50mm × 200mm.
[0230] The positive electrode obtained in (1-7) is cut into a rectangular positive electrode of 45mm×150mm.
[0231] The negative electrode obtained in (1-6) is cut into a rectangular negative electrode of 47mm×155mm.
[0232] The rectangular positive electrode, rectangular spacer, and rectangular negative electrode are stacked sequentially along their long sides and then wound together to form a wound body.
[0233] The wound material was placed inside an aluminum packaging material outer casing. Then, a 1.0M LiPF6 solution (a mixed solvent of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (volume ratio), containing 2% by mass of ethylene carbonate as an additive) was filled into the aluminum packaging material outer casing as the electrolyte. The opening of the aluminum packaging material outer casing was further sealed by heat sealing at 150°C to manufacture a lithium-ion secondary battery. The capacity retention of the obtained lithium-ion secondary battery was evaluated. The results are shown in Table 1.
[0234] (Example 2)
[0235] In the preparation of the water-soluble polymer in (1-2), a composition consisting of only 100.0 parts of acrylic acid (excluding acrylonitrile) was used as the monomer composition for the water-soluble polymer. Otherwise, the binder composition, negative electrode, and lithium-ion secondary battery were obtained and evaluated by the same procedure as in Example 1. The results are shown in Table 1.
[0236] (Example 3)
[0237] (3-1. Particulate polymer B ~ binder composition)
[0238] 100 parts of the monomer composition, 0.25 parts of tert-dodecyl mercaptan as a chain transfer agent, and 0.35 parts of sodium lauryl sulfate as an emulsifier were added to container A to prepare a mixture containing the monomer composition. The monomer composition was composed of 35.0 parts of styrene as an aromatic vinyl monomer, 51.0 parts of 1,3-butadiene as an aliphatic conjugated diene monomer, 10.0 parts of acrylonitrile as a nitrile-containing vinyl monomer, and 4.0 parts of itaconic acid as an acidic monomer.
[0239] On the other hand, prepare 1 part of potassium persulfate as a polymerization initiator.
[0240] The mixture is initially added from container A in small amounts to pressure container B, while the polymerization initiator is simultaneously added in small amounts to pressure container B, thereby initiating the polymerization reaction. The reaction temperature is maintained at 75°C.
[0241] After 5.5 hours of polymerization initiation, the full amount of these monomer compositions was added, and then the mixture was further heated to 85°C and reacted for 6 hours.
[0242] The reaction was terminated by cooling at a polymerization conversion rate of 97%, yielding a mixture containing particulate polymer. A 5% sodium hydroxide aqueous solution was added to this mixture to adjust the pH to 8. Unreacted monomers were then removed by heated vacuum distillation. The mixture was then cooled and passed through a magnetic filter. This yielded an aqueous dispersion of particulate polymer B as a binder composition. The solids concentration of the binder composition was 40%. The redox potential, surface acidity, acidity in the aqueous phase, and metal content of the binder composition were measured. Furthermore, the storage stability of the binder composition was evaluated. The results are shown in Table 1.
[0243] (3-2. Negative electrode and lithium-ion secondary battery)
[0244] The binder composition obtained in (3-1) was used instead of the binder composition obtained in (1-3) of Example 1. Otherwise, the negative electrode and lithium-ion secondary battery were obtained and evaluated by the same operation as in (1-4) to (1-8) of Example 1. The results are shown in Table 1.
[0245] (Example 4)
[0246] (4-1. Particulate polymer C)
[0247] In a reactor equipped with a stirrer, 96.0 parts of butyl acrylate as a (meth)acrylate monomer, 2.0 parts of acrylonitrile as a cyanide-based monomer, 2.0 parts of methacrylic acid as an acidic monomer, 0.3 parts of sodium dodecylbenzenesulfonate as an emulsifier, 0.3 parts of ammonium persulfate as a polymerization initiator, and 300 parts of deionized water were added. After thorough stirring, the mixture was heated to 70°C for 4 hours, and then heated to 80°C for aging for 3 hours to complete the reaction. The reaction mixture was then cooled to below 30°C to obtain an aqueous dispersion containing particulate polymer C.
[0248] (4-2. Adhesive composition)
[0249] Aqueous dispersions containing particulate polymer A obtained in Example 1 (1-1) with 90.0 parts (based on the mass of the particulate polymer) of aqueous dispersions containing particulate polymer C obtained in Example 1 (4-1) were mixed and then passed through a magnetic filter. This yielded an aqueous dispersion containing particulate polymers A and C as a binder composition.
[0250] (4-3. Negative electrode and lithium-ion secondary battery)
[0251] The binder composition obtained in (4-2) was used instead of the binder composition obtained in (1-3) of Example 1. Otherwise, the negative electrode and lithium-ion secondary battery were obtained and evaluated by the same operation as in (1-4) to (1-8) of Example 1. The results are shown in Table 1.
[0252] (Example 5)
[0253] In preparing the particulate polymer B of (3-1), a composition consisting of 9.0 parts styrene, 56.0 parts butadiene, 25.0 parts acrylonitrile, and 10.0 parts acrylic acid was used as the monomer composition. Otherwise, the binder composition, negative electrode, and lithium-ion secondary battery were obtained and evaluated by the same procedure as in Example 3. The results are shown in Table 1.
[0254] (Comparative Example 1)
[0255] In preparing the particulate polymer B of (3-1), a composition consisting of 51.0 parts styrene, 49.0 parts butadiene, and 0.1 parts itaconic acid was used in total of 100.1 parts. Otherwise, the binder composition, negative electrode, and lithium-ion secondary battery were obtained and evaluated by the same procedure as in Example 3. The results are shown in Table 1.
[0256] (Comparative Example 2)
[0257] In preparing the particulate polymer B of (3-1), a composition consisting of 45.0 parts styrene, 40.0 parts butadiene, 3.0 parts methyl methacrylate, and 12.0 parts acrylic acid was used as the monomer composition. Otherwise, the binder composition, negative electrode, and lithium-ion secondary battery were obtained and evaluated by the same procedure as in Example 3. The results are shown in Table 1.
[0258] (Comparative Example 3)
[0259] Except for the following changes, the binder composition, negative electrode, and lithium-ion secondary battery were obtained and evaluated through the same procedures as in Example 3. The results are shown in Table 1.
[0260] • When preparing the particulate polymer B of (3-1), a composition consisting of 24.0 parts styrene, 72.0 parts butadiene and 4.0 parts itaconic acid is used as the monomer composition.
[0261] • When preparing the particulate polymer B in (3-1), the step of passing it through a magnetic filter was not performed.
[0262] (Comparative Example 4)
[0263] In the preparation of the water-soluble polymer in (1-2), a composition consisting of 40.0 parts acrylic acid and 60.0 parts acrylonitrile was used as the monomer composition for the water-soluble polymer. Otherwise, the binder composition, negative electrode, and lithium-ion secondary battery were obtained and evaluated by the same procedure as in Example 1. The results are shown in Table 1.
[0264] [Table 1]
[0265] Table 1
[0266]
[0267] St: Parts by weight of styrene used
[0268] BD mass fraction: Mass fraction of 1,3-butadiene used
[0269] Ester mass fraction: Mass fraction of (meth)acrylate monomer (2-hydroxyethyl acrylate) used
[0270] Other (AN) parts by weight: Parts by weight of other monomers (acrylonitrile) used.
[0271] Parts by mass of monomers containing acidic groups: Parts by mass of the monomers containing acidic groups used (itaconic acid, methacrylic acid, acrylic acid).
[0272] AA (parts by weight): Parts by weight of acrylic acid used
[0273] AN (parts by weight): Parts by weight of acrylonitrile used
[0274] Metal content (ppm): The content of Fe, Cu, Zn, Co, Ni, and Cr as determined by ICP-MS. "0.5>": All less than 0.5 ppm. "1.0>": Any one or more elements are above 0.5 ppm but less than 1.0 ppm.
[0275] As can be seen from the above results, the binder composition of the embodiments has higher storage stability, can achieve electrodes with high peeling characteristics, and can achieve non-aqueous secondary batteries with high cycle characteristics compared with the binder composition of the comparative examples.
[0276] In addition to the above evaluation, the degree of roller contamination during the pressing operation of the roller press in the manufacture of the negative electrode was visually evaluated. The results showed no contamination in Examples 1-5, Comparative Examples 1 and 4, allowing for good pressing operations. However, roller contamination occurred in Comparative Examples 2-3, requiring frequent cleaning. Furthermore, this roller contamination is considered one of the reasons for the decrease in peel strength.
Claims
1. A binder composition for a non-aqueous secondary battery electrode, comprising a particulate polymer and a dispersion medium, and having an aqueous phase and a solid phase, The redox potential of the adhesive composition is 90–280 mV. The total acid content on the surface of the particulate polymer and the acid content in the aqueous phase is greater than 0.15 mmol / g and less than 1.5 mmol / g.
2. The binder composition for non-aqueous secondary battery electrodes according to claim 1, wherein, The contents of Fe, Cu, Zn, Co, Ni and Cr are all less than 0.5 ppm.
3. The binder composition for non-aqueous secondary battery electrodes according to claim 1, wherein, The value obtained by dividing the amount of acid contained in the aqueous phase by the sum of the amount of acid in the aqueous phase and the amount of acid on the surface of the particulate polymer is 0.2 or more and 0.6 or less.
4. The binder composition for non-aqueous secondary battery electrodes according to claim 1, wherein, The particulate polymer comprises one or more selected from styrene monomer units, butadiene monomer units, (meth)acrylate monomer units, and monomer units containing acidic groups.
5. The binder composition for non-aqueous secondary battery electrodes according to claim 1, wherein, The binder composition for the non-aqueous secondary battery electrode also includes a water-soluble polymer.
6. A slurry composition for a non-aqueous secondary battery electrode, comprising an electrode active material and a binder composition for a non-aqueous secondary battery electrode according to any one of claims 1 to 5.
7. An electrode for a non-aqueous secondary battery, having an electrode composite material layer formed using the slurry composition for a non-aqueous secondary battery electrode as described in claim 6.
8. A non-aqueous secondary battery having a positive electrode, a negative electrode, a spacer and an electrolyte, wherein at least one of the positive electrode and the negative electrode is an electrode for a non-aqueous secondary battery as described in claim 7.
Citation Information
Patent Citations
Electrode for secondary battery, binder for secondary battery electrode, manufacturing method and secondary battery
JP2012204303A
Method for manufacturing nonaqueous secondary battery
JP2013045714A
Negative electrode slurry, negative electrode, and secondary battery
JP2022064465A
Binder composition for secondary battery, slurry composition for secondary battery functional layer, secondary battery member, secondary battery, and method of producing slurry composition for secondary battery negative electrode
US20200411870A1
Negative electrode slurry, negative electrode, and rechargeable battery
US20220115665A1